At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Sure! Let's find the matrices [tex]\( A \)[/tex] and [tex]\( B \)[/tex] based on the given equations:
1. [tex]\( 2A - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \)[/tex]
2. [tex]\( 2B + A = \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \)[/tex]
To solve these equations step-by-step:
### Step 1: Isolate [tex]\( A \)[/tex]
First, we can manipulate these equations to isolate one of the matrices. Let's solve for [tex]\( A \)[/tex] first.
Equation 1: [tex]\( 2A - B = \mathbf{X} \)[/tex], where [tex]\( \mathbf{X} = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \)[/tex].
Multiply the whole equation by 2:
[tex]\[ 4A - 2B = 2\mathbf{X} \][/tex]
This results in:
[tex]\[ 4A - 2B = \begin{bmatrix} 12 & -12 & 0 \\ -8 & 4 & 2 \end{bmatrix} \][/tex]
Equation 2: [tex]\( 2B + A = \mathbf{Y} \)[/tex], where [tex]\( \mathbf{Y} = \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \)[/tex].
Add the two equations together:
[tex]\[ 4A - 2B + 2B + A = \begin{bmatrix} 12 & -12 & 0 \\ -8 & 4 & 2 \end{bmatrix} + \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \][/tex]
[tex]\[ 5A = \begin{bmatrix} 15 & -10 & 5 \\ -10 & 5 & -5 \end{bmatrix} \][/tex]
Now, divide both sides by 5:
[tex]\[ A = \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} \][/tex]
### Step 2: Solve for [tex]\( B \)[/tex]
Now that we have [tex]\( A \)[/tex], substitute it back into one of the original equations to solve for [tex]\( B \)[/tex].
We'll use the equation [tex]\( 2A - B = \mathbf{X} \)[/tex]:
[tex]\[ 2A - B = \mathbf{X} \][/tex]
[tex]\[ 2 \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
[tex]\[ \begin{bmatrix} 6 & -4 & 2 \\ -4 & 2 & -2 \end{bmatrix} - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
Rearrange to isolate [tex]\( B \)[/tex]:
[tex]\[ B = \begin{bmatrix} 6 & -4 & 2 \\ -4 & 2 & -2 \end{bmatrix} - \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 0 & 2 & 2 \\ 0 & 0 & -3 \end{bmatrix} \][/tex]
### Final Matrices
Therefore, the solutions for [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are:
[tex]\[ A = \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 0 & 2 & 2 \\ 0 & 0 & -3 \end{bmatrix} \][/tex]
1. [tex]\( 2A - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \)[/tex]
2. [tex]\( 2B + A = \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \)[/tex]
To solve these equations step-by-step:
### Step 1: Isolate [tex]\( A \)[/tex]
First, we can manipulate these equations to isolate one of the matrices. Let's solve for [tex]\( A \)[/tex] first.
Equation 1: [tex]\( 2A - B = \mathbf{X} \)[/tex], where [tex]\( \mathbf{X} = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \)[/tex].
Multiply the whole equation by 2:
[tex]\[ 4A - 2B = 2\mathbf{X} \][/tex]
This results in:
[tex]\[ 4A - 2B = \begin{bmatrix} 12 & -12 & 0 \\ -8 & 4 & 2 \end{bmatrix} \][/tex]
Equation 2: [tex]\( 2B + A = \mathbf{Y} \)[/tex], where [tex]\( \mathbf{Y} = \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \)[/tex].
Add the two equations together:
[tex]\[ 4A - 2B + 2B + A = \begin{bmatrix} 12 & -12 & 0 \\ -8 & 4 & 2 \end{bmatrix} + \begin{bmatrix} 3 & 2 & 5 \\ -2 & 1 & -7 \end{bmatrix} \][/tex]
[tex]\[ 5A = \begin{bmatrix} 15 & -10 & 5 \\ -10 & 5 & -5 \end{bmatrix} \][/tex]
Now, divide both sides by 5:
[tex]\[ A = \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} \][/tex]
### Step 2: Solve for [tex]\( B \)[/tex]
Now that we have [tex]\( A \)[/tex], substitute it back into one of the original equations to solve for [tex]\( B \)[/tex].
We'll use the equation [tex]\( 2A - B = \mathbf{X} \)[/tex]:
[tex]\[ 2A - B = \mathbf{X} \][/tex]
[tex]\[ 2 \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
[tex]\[ \begin{bmatrix} 6 & -4 & 2 \\ -4 & 2 & -2 \end{bmatrix} - B = \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
Rearrange to isolate [tex]\( B \)[/tex]:
[tex]\[ B = \begin{bmatrix} 6 & -4 & 2 \\ -4 & 2 & -2 \end{bmatrix} - \begin{bmatrix} 6 & -6 & 0 \\ -4 & 2 & 1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 0 & 2 & 2 \\ 0 & 0 & -3 \end{bmatrix} \][/tex]
### Final Matrices
Therefore, the solutions for [tex]\( A \)[/tex] and [tex]\( B \)[/tex] are:
[tex]\[ A = \begin{bmatrix} 3 & -2 & 1 \\ -2 & 1 & -1 \end{bmatrix} \][/tex]
[tex]\[ B = \begin{bmatrix} 0 & 2 & 2 \\ 0 & 0 & -3 \end{bmatrix} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.